Islamic Religious Education Learning Strategy Based on Self-Regulated Learning in Enhancing Students' Metacognition at Al-Izzah International Islamic Boarding School - Komariyatul Mahmuda; Mohammad Asrori; Ahmad Sholeh (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Islamic Religious Education Learning Strategy Based on Self-Regulated Learning in Enhancing Students' Metacognition at Al-Izzah International Islamic Boarding SchoolObjective: This study aims to analyze the learning strategies employed by teachers to enhance students' metacognition through a Self-Regulated Learning (SRL) approach at Al-Izzah IIBS Batu High School. Method: This study employs a qualitative approach, utilizing a case study design. Data was obtained through interviews with the principal, vice principal for curriculum, Islamic Education teachers, homeroom teachers, and students. Results: The improvement of students' metacognition at SMA Al-Izzah IIBS Batu is achieved through a Self-Regulated Learning (SRL)-based Islamic Religious Education teaching strategy that involves teacher reflection and the development of students' learning independenc. Conclusion: Students' self-regulated learning (SRL) abilities influence their metacognition, which, in turn, shapes their learning independence and readiness to become lifelong learners. Contribution: This study contributes to the implementation of Self-Regulated Learning in Islamic Religious Education, enhancing metacognition and fostering life skills such as independence, responsibility, and self-awareness among students.INDOENSIAN: Strategi Pembelajaran Pendidikan Agama Islam Berbasis Self-Regulated Learning Dalam Meningkatkan Metakognisi Siswa di Al-Izzah International Islamic Boarding SchoolTujuan: Penelitian ini bertujuan untuk menganalisis strategi pembelajaran yang dilakukan oleh guru dalam meningkatkan metakognisi siswa melalui pendekatan berbasis Self Regulated Learning (SRL) di SMA Al-Izzah IIBS Batu. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Data diperoleh melalui wawancara dengan kepala sekolah, waka kurikulum, guru Pendidikan Agama Islam, wali kelas dan siswa. Hasil: Peningkatan metakognisi siswa di SMA Al-Izzah IIBS Batu tercapai melalui strategi pembelajaran Pendidikan Agama Islam berbasis Self-Regulated Learning (SRL), yang melibatkan refleksi guru dan pengembangan kemandirian belajar siswa. Kesimpulan: Kemampuan Self-Regulated Learning (SRL) peserta didik memberikan pengaruh terhadap metakognisinya, yang pada akhirnya membentuk kemandirian belajar dan kesiapan menjadi pembelajar sepanjang hayat secara berkelanjutan. Kontribusi: Penelitian ini berkontribusi dalam penerapan Self-Regulated Learning pada pembelajaran Pendidikan Agama Islam, yang meningkatkan metakognisi dan menumbuhkan keterampilan hidup seperti kemandirian, tanggung jawab, dan kesadaran diri pada peserta didik.